Financial management for nonprofit organizations : policies and practices - Zietlow, John T. (Wiley, 2018)
Essential tools and guidance for effective nonprofit financial management Financial Management for Nonprofit Organizations provides students, professionals, and board members with a comprehensive reference for the field. Identifying key objectives and exploring current practices, this book offers practical guidance on all major aspects of nonprofit financial management. As nonprofit organizations fall under ever-increasing scrutiny and accountability, this book provides the essential knowledge and tools professional need to maintain a strong financial management system while serving the organization's stated mission. Financial management, cash flow, and financial sustainability are perennial issues, and this book highlights the concepts, skills, and tools that help organizations address those issues. Clear guidance on analytics, reporting, investing, risk management, and more comprise a singular reference that nonprofit finance and accounting professionals and board members should keep within arm's reach. Updated to reflect the post-recession reality and outlook for nonprofits, this new edition includes new examples, expanded tax-exempt financing material, and recession analysis that informs strategy going forward. Articulate the proper primary financial objective, target liquidity, and how it ensures financial health and sustainability Understand nonprofit financial practices, processes, and objectives Manage your organization's resources in the context of its mission Delve into smart investing and risk management best practices Manage liquidity, reporting, cash and operating budgets, debt and other liabilities, IP, legal risk, internal controls and more Craft appropriate financial policies Although the U.S. economy has recovered, recovery has not addressed the systemic and perpetual funding challenges nonprofits face year after year. Despite positive indicators, many organizations remain hampered by pursuit of the wrong primary financial objective, insufficient funding and a lack of investment in long-term sustainability; in this climate, financial managers must stay up-to-date with the latest tools, practices, and regulations in order to serve their organization's interests. Financial Management for Nonprofit Organizations provides clear, in-depth reference and strategy for navigating the expanding financial management function.